Family Troubles? : Exploring Changes and Challenges in the Family Lives of Children and Young People - Gillies, Val; Hooper, Carol-Ann, 1956-; Ribbens McCarthy, Jane (Book collections on Project MUSE., 2013)
This title takes a fresh look at how 'troubles' feature in 'normal' families, and how the 'normal' features in troubled families. In addressing chapter draw on research on a wide range of substantive topics including infant care, sibling conflict, divorce, disability, illness, migration and asylum-seeking, substance misuse, violence, kinship care, and forced marriage.